2013
DOI: 10.1075/lia.4.2.06vra
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the upper limits of the Aspect Hypothesis

Abstract: This paper explores coalitions between tense-aspect morphology and the aspectual class of predicates in second language acquisition (the Aspect Hypothesis) on the basis of 36 oral narratives elicited with a picture book from French L1 adult learners of English. The observed distributional patterns are analysed in relation to the prototypical inflection/predicate coalitions observed both at early stages of L2 development and in English L1. While advanced learners are expected to make a productive use of tense-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…John Benjamins Publishing Company All rights reserved plusieurs chercheurs ont identifié des facteurs linguistiques contraignant les choix de marqueurs. Parmi ces derniers, on relève le rôle joué par l'aspect lexical et les propriétés sémantiques des prédicats, qui influent sur le développement temporoaspectuel, en lien avec l'hypothèse de la 'Primauté de l'Aspect' (voir Collins 2002 ;Rohde 1996 ;Salaberry 1998 ;Vraciu 2013) ; mais aussi le rôle de contraintes discursives (marquage de la trame et de l'arrière-plan) (voir Bardovi-Harlig 1999, 2000Noyau 1991), et le rôle de la saillance phonétique dans le marquage des formes irrégulières par rapport aux formes régulières (voir Bayley 1996 ;Housen 2002). Si les perspectives théoriques de ces études se fondant sur des corpus de productions d'apprenants sont très variées (formelle, fonctionnaliste, variationniste), d'autres études visant la compréhension ont été menées dans une perspective générativiste (voir par exemple Ayoun 2013 ;Montrul & Slabakova 2003).…”
Section: Pascale Leclercq Et Martin Howardunclassified
See 1 more Smart Citation
“…John Benjamins Publishing Company All rights reserved plusieurs chercheurs ont identifié des facteurs linguistiques contraignant les choix de marqueurs. Parmi ces derniers, on relève le rôle joué par l'aspect lexical et les propriétés sémantiques des prédicats, qui influent sur le développement temporoaspectuel, en lien avec l'hypothèse de la 'Primauté de l'Aspect' (voir Collins 2002 ;Rohde 1996 ;Salaberry 1998 ;Vraciu 2013) ; mais aussi le rôle de contraintes discursives (marquage de la trame et de l'arrière-plan) (voir Bardovi-Harlig 1999, 2000Noyau 1991), et le rôle de la saillance phonétique dans le marquage des formes irrégulières par rapport aux formes régulières (voir Bayley 1996 ;Housen 2002). Si les perspectives théoriques de ces études se fondant sur des corpus de productions d'apprenants sont très variées (formelle, fonctionnaliste, variationniste), d'autres études visant la compréhension ont été menées dans une perspective générativiste (voir par exemple Ayoun 2013 ;Montrul & Slabakova 2003).…”
Section: Pascale Leclercq Et Martin Howardunclassified
“…From this point of view, many studies have suggested that different linguistic factors may constrain the learner's choice of markers. Such factors concern the inherent lexical aspect of the predicate in relation to its semantic properties which appear to impact temporal-aspectual development, as proposed by the Primacy of Aspect Hypothesis (see Collins 2002;Rohde 1996;Salaberry 1998;Vraciu 2013); discourse factors (particularly the foreground/background distinction, see Bardovi-Harlig 1999, 2000Noyau 1991), and saliency factors such as the phonetic differences between regular and irregular verb forms (see Bayley 1996;Housen 2002). While such work is based on studies of spoken and written corpora from within different theoretical perspectives such as formal, functionalist and variationist approaches, other studies have focused on comprehension within a Universal Grammar framework (see, for example, Ayoun 2013;Montrul & Slabakova 2003).…”
Section: Introductionmentioning
confidence: 99%